2022
DOI: 10.1186/s12967-022-03637-8
|View full text |Cite
|
Sign up to set email alerts
|

Detecting associated genes for complex traits shared across East Asian and European populations under the framework of composite null hypothesis testing

Abstract: Background Detecting trans-ethnic common associated genetic loci can offer important insights into shared genetic components underlying complex diseases/traits across diverse continental populations. However, effective statistical methods for such a goal are currently lacking. Methods By leveraging summary statistics available from global-scale genome-wide association studies, we herein proposed a novel genetic overlap detection method called CONTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…However, the design discrepancies are difficult to handle with only summary statistics, a comprehensive investigation regarding these discrepancies needs individual-level data, and is thus impeded by privacy concerns when sharing data [ 88 ]. To handle the potential discrepancy of LD in various populations, we previously conducted a gene-based replicability analysis in the EAS and EUR populations [ 89 ], where we aggregated multiple SNP-level association signs into a single gene-level association sign while taking LD into account.…”
Section: Discussionmentioning
confidence: 99%
“…However, the design discrepancies are difficult to handle with only summary statistics, a comprehensive investigation regarding these discrepancies needs individual-level data, and is thus impeded by privacy concerns when sharing data [ 88 ]. To handle the potential discrepancy of LD in various populations, we previously conducted a gene-based replicability analysis in the EAS and EUR populations [ 89 ], where we aggregated multiple SNP-level association signs into a single gene-level association sign while taking LD into account.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the two path association tests in our mediation analysis can be implemented by an equivalent manner of variance-component based score tests under the context of mixed models. It has been demonstrated that the variance component test is often more powerful compared to its counterpart such as multivariate Wald test (43,44,46,(73)(74)(75)(76).…”
Section: Discussionmentioning
confidence: 99%
“…To effectively detect the existence of mediation effect with highdimensional mediators, we first employ the variance componentbased score test in a linear mixed model via an inverse transformation to assess the association between childhood maltreatment and a group of DNA methylation CpG sites, and then test for the effect of DNA methylation on the disorder of focus while adjusting for the direct influence of childhood maltreatment within the framework of linear mixed-effects model (43)(44)(45)(46). We finally determine whether the mediation effect of DNA methylation exists by following the main idea proposed in Liu et al (41), which can lead to desirable type I error rate control and higher power compared to existing mediation effect test methods.…”
Section: Introductionmentioning
confidence: 99%